Racism and Discrimination in South Africa’s Apartheid Tourism Landscape - Christian Rogerson (Studia Periegetica)
Tourism scholarship has devoted only a small amount of attention to issues around racial discrimination. This article represents a novel contribution to historical research on racial discrimination and understanding the racialization of tourism landscapes. Under scrutiny is the case of South Africa with its extensive history of racial discrimination during the years of apartheid. As context, the study is situated against the historical record of the racialized landscape of tourism during the Jim Crow era in the United States. Using a range of archival material and secondary sources an analysis is presented of the restricted mobilities of the African population, the evolution of segregated tourism spaces and the contours of the racialized tourism landscape of apartheid. The production of a series of guidebooks in the 1960s by the South African Institute of Race Relations to assist Africans navigate the hostile tourism environment is argued to be comparable, in many respects, to the Green Books of Jim Crow USA.